Innovation in processing household waste into eco-enzymes in the community in Merak Batin village - Ade Lenty Hoya; Jaenal Abidin; Baharudin Baharudin (Abdimas Paspama, 2024)
Citerep Hamlet is one of the hamlets in Merak Batin Village, Natar District, South Lampung Regency, Lampung Province. This village is dominated by residential land covering an area of ​​1,351 hectares which results in a lot of human activity which cannot be separated from waste or rubbish, especially household waste.. There is no final disposal site (TPA) around Citerep Hamlet and a lack of rubbish dumps. The aim of this activity is to provide outreach and training to the Citerep Hamlet community regarding the use of organic waste into ecoenzymes. The method used is the socialization and training method. The target audience for the service is a sample of at least 20 residents to serve as socialization and training participants. The activity implementation stage includes the initial stage, core and closing stages. The initial stage consists of an interview process, socialization, andtraining manufacture of ecoenzymes. The closing stage is post-activity evaluation. The results can increase people's knowledge and make people independent by making ecoenzymes at home and being able to process organic waste, especially vegetable and fruit waste, into useful products. Innovation in processing household waste in the manufacture of ecoenzymes is a solution for reducing the waste that occurs.